Hydrodynamic interactions in multiple body array: a simple and fast approach coupling boundary element method and plane wave approximation - Singh, Jitendra; Babarit, Aurélien (Volume 5: Ocean Engineering, 2013)
ASME 2013 32nd International Conference on Ocean, Offshore and Arctic EngineeringVolume 5: Ocean EngineeringNantes, France, June 9–14, 2013Conference Sponsors: Ocean, Offshore and Arctic Engineering DivisionISBN: 978-0-7918-5539-3 International audience The hydrodynamic forces acting on an isolated body could be considerably different than those when it is considered in an array of multiple bodies, due to wave interactions among them. In this context, we present in this paper a numerical approach based on the linear potential flow theory to solve full hydrodynamic interaction problem in a multiple body array. In contrast to the previous approaches that considered all bodies in an array as a single unit, the present approach relies on solving for an isolated body. The interactions among the bodies are then taken into account via plane wave approximation in an iterative manner. The boundary value problem corresponding to a isolated body is solved by the Boundary Element Method (BEM). The approach is useful when the bodies are sufficiently distant from each other, at-least greater than five times the characteristic dimensions of the body. This is a valid assumption for wave energy converter devices array of point absorber type, which is our target application at a later stage. The main advantage of the proposed approach is that the computational time requirement is significantly less than the commonly used direct BEM. The time savings can be realized for even small arrays consisting four bodies. Another advantage is that the computer memory requirements are also significantly smaller compared to the direct BEM, allowing us to consider large arrays. The numerical results for hydrodynamic interaction problem in two arrays consisting of 25 cylinders and same number of rectangular flaps are presented to validate the proposed approach.